2021
DOI: 10.6065/apem.2040202.101
|View full text |Cite
|
Sign up to set email alerts
|

Features of partial remission in children with type 1 diabetes using the insulin dose-adjusted A1c definition and risk factors associated with nonremission

Abstract: We sought to evaluate features of partial remission (PR) in children with type 1 diabetes mellitus (T1DM) using the insulin-dose adjusted A1c (IDAA1c) definition and to identify risk factors associated with nonremission. Methods: Medical records of patients with newly diagnosed T1DM between January 1, 2008, and June 30, 2018, were retrospectively reviewed. Hemoglobin A1c (HbA1c) readings and insulin total daily doses (TDDs) of each patient at each follow-up visit were obtained with IDAA1c values calculated. PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Another factor of remission identified by our study was the severity of diabetes at the onset, as the remitters had significantly lower HbA1c levels at the time of diagnosis. Higher HbA1c levels reflect longer duration and higher values of hyperglycaemia prior to the diagnosis of diabetes and was also described by Wong et al as a negative factor for remission 22 . In our univariate analyses we also found other factors of remission onset linked to the lower severity of diabetes previously described by others, i.e.…”
Section: Discussionsupporting
confidence: 54%
“…Another factor of remission identified by our study was the severity of diabetes at the onset, as the remitters had significantly lower HbA1c levels at the time of diagnosis. Higher HbA1c levels reflect longer duration and higher values of hyperglycaemia prior to the diagnosis of diabetes and was also described by Wong et al as a negative factor for remission 22 . In our univariate analyses we also found other factors of remission onset linked to the lower severity of diabetes previously described by others, i.e.…”
Section: Discussionsupporting
confidence: 54%
“…In general, children experience remission to a higher extend than adults, and within the first group, the probability of remaining in remission is greater as the onset age increased (70). Different regression analyses showed that higher pH and bicarbonate levels, higher BMI, male sex, and lower HbA1c, insulin dose, and numbers of islet antibodies at T1D onset are predictors of remission (13,14,(70)(71)(72). However, the prediction of remission using immunological data is rather scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the mechanisms underlying the PR phase are poorly characterized, but this natural phenomenon has been attributed to both the reduction of glucose toxicity after the initiation of the insulin therapy and the consequent β-cell rest, recovery, and regeneration with improved endogenous insulin production ( 12 ). At a clinical level, bicarbonate concentrations >15 mg/dl, age >5 years, male sex, higher body mass index (BMI) values, lower HbA1c levels, and <3 diabetes-associated autoantibodies can predispose to PR in children and adolescents with new-onset T1D ( 13 , 14 ). Furthermore, mechanisms of immune regulation are non-linear along the natural history of T1D—matching well with the proposed relapsing-remitting character of the disease course—and the PR phase is associated with these immunomodulatory changes ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating the epidemiology of remission in children with T1DM demonstrated that various parameters could affect the development of PR. 2,[23][24][25][26] In some publications, it has been reported that female patients with T1DM need more exogenous insulin than males during both the prepubertal and pubertal periods. 27,28 Furthermore, it is known that the insulin sensitivity of patients with T1DM differs in a wide range and is lower in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, after adjustment, the only independent factor facilitating the development of PR was male sex. Previous studies investigating the epidemiology of remission in children with T1DM demonstrated that various parameters could affect the development of PR 2,23–26 . In some publications, it has been reported that female patients with T1DM need more exogenous insulin than males during both the prepubertal and pubertal periods 27,28 .…”
Section: Discussionmentioning
confidence: 99%